2011
DOI: 10.1108/13683041111161139
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the RSQS in apparel specialty stores

Abstract: PurposeThe purpose of this study is to validate the Retail Service Quality Scale (RSQS) developed by Dabholkar et al. in the Malaysian business setting, specifically in the context of apparel specialty stores.Design/methodology/approachTwo well‐known retail clothing store chains were selected for this study. Purposive sampling method was used, with a total of 211 responses collected from customers of all X and Y's chain stores in the northern region of Malaysia.FindingsThe paper finds that all the five dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The coefficient associated with buying wine from a store that has won some awards (RSKREDS5) is significant at the 10% level of confidence and both have positive signs. Our findings support the work of Ai Leen and Ramayah (2011) who explored the customer service components of Starbucks, finding that the company offered a friendly and fulfilling experience. Similar results have been reported by Esbjerg et al (2012), White and Klinner (2012) along with Lockshin and Kahrimanis (1998) who all found that retail stores with courteous and knowledgeable staff are able to instil confidence in consumers and build affective bonds with them.…”
Section: Results Of Ordered Probit Regressionsupporting
confidence: 92%
See 1 more Smart Citation
“…The coefficient associated with buying wine from a store that has won some awards (RSKREDS5) is significant at the 10% level of confidence and both have positive signs. Our findings support the work of Ai Leen and Ramayah (2011) who explored the customer service components of Starbucks, finding that the company offered a friendly and fulfilling experience. Similar results have been reported by Esbjerg et al (2012), White and Klinner (2012) along with Lockshin and Kahrimanis (1998) who all found that retail stores with courteous and knowledgeable staff are able to instil confidence in consumers and build affective bonds with them.…”
Section: Results Of Ordered Probit Regressionsupporting
confidence: 92%
“…Lockshin and Kahrimanis (1998) and Boatto, Defrancesco, and Trestini (2011) found buyers do not distinguish perceptually between stores that have different names and managerial control if they have similar attributes. For a store to have a competitive advantage over others, the store must adopt an expert-based approach by hiring and training staff to be friendly and knowledgeable as front line employees who represent the store and perform a marketing function (Ai Leen & Ramayah, 2011;Boatto et al, 2011;Esbjerg et al, 2012;Lockshin & Kahrimanis, 1998;White & Klinner, 2012).…”
Section: Expert Service (Values Delivery) By Retailersmentioning
confidence: 99%
“…Yuen and Chan (2010) performed a study on a window curtain retailer in Hong Kong. Leen and Ramayah (2011) performed a study of apparel stores in Malaysia. Ahmad, Ihtiyar, and Omar (2014) performed a comparative study for grocery retailers in Malaysia and Turkey.…”
Section: Retail Service Qualitymentioning
confidence: 99%
“…The object of belief can be a person, a group of people, an institution, behavior, a policy or an event, and the connected attribute may be any object, trait, property, quality, characteristic, outcome or event. However, Leen and Ramayah (2011) defined that beliefs are the feeling towards some aspects of the world, which correspond to a person's self-understanding and environment and lead to the person's attitude, intention, and behavior. They added that perceived usefulness and perceived ease of use are two beliefs that determine the likelihood of online shopping as argued by Vijayasarathy (2004) and Yoon (2010).…”
Section: General Belief About Online Shoppingmentioning
confidence: 99%